ANALYSIS OF SOCIO-ECONOMIC CHARACTERISTICS OF HOUSEHOLD CATFISH FARMERS IN PALEMBANG CITY - Ningrum, Anilda Satya; Ariyani, Desi; Amin, Mohamad (Jurnal Perikanan Unram, 2025)
Catfish farming is one of the rapidly growing fisheries sectors in urban areas, including Palembang City. However, the success of this business is greatly influenced by the socio-economic conditions of the farmers. A common problem faced is the lack of information about the socio-economic characteristics of catfish farming households, which can serve as a basis for policy formulation in developing aquaculture businesses. This study aims to identify the socio-economic characteristics of catfish farming households in Palembang City.This research uses a descriptive method and collects data through questionnaires and direct interviews with farmers in the districts of Plaju, Sematang Borang, Gandus, and Sukarami. The results indicate that 63% of farmers have completed senior high school education, 43% are in the productive age range of 41–50 years, and 51% have less than 10 years of work experience. Most farmers (70%) own farming land measuring 1,100–2,000 m², classified as medium-scale enterprises. Economically, 53 respondents earn additional income from agricultural activities such as patin fish farming, while 47 respondents earn income from non-agricultural sectors. The average monthly operational cost of catfish farming reaches IDR 10,887,512, dominated by variable costs amounting to IDR 8,839,525. These findings reflect the importance of understanding socio-economic conditions in the sustainable development of catfish farming businesses.